2016
DOI: 10.1186/s12974-016-0676-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of aspirin-triggered resolvin D1 on spinal nociceptive processing in rat pain models

Abstract: BackgroundHarnessing the actions of the resolvin pathways has the potential for the treatment of a wide range of conditions associated with overt inflammatory signalling. Aspirin-triggered resolvin D1 (AT-RvD1) has robust analgesic effects in behavioural models of pain; however, the potential underlying spinal neurophysiological mechanisms contributing to these inhibitory effects in vivo are yet to be determined. This study investigated the acute effects of spinal AT-RvD1 on evoked responses of spinal neurones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…The lack of effect of AT-RvD1 on WDR neuronal responses to higher weight mechanical stimuli suggests that treatments acting through the resolvin pathways are unlikely to modulate normal physiological high-intensity nociceptive processing, ensuring that this major protective pathway remains intact and functional. Indeed, our previous study reported no effect of AT-RvD1 on electrically evoked C-fibre responses of WDR neurones in naïve rats [22] and behavioural studies reported no change in baseline threshold responses following spinal RvD1 treatment [61]. Our data build upon the recent report that intrathecal injection of RvD1 attenuates mechanical hypersensitivity in PCX-treated mice [21], and provides neurophysiological mechanisms underlying these antihyperalgesic effects seen in models of CINP.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The lack of effect of AT-RvD1 on WDR neuronal responses to higher weight mechanical stimuli suggests that treatments acting through the resolvin pathways are unlikely to modulate normal physiological high-intensity nociceptive processing, ensuring that this major protective pathway remains intact and functional. Indeed, our previous study reported no effect of AT-RvD1 on electrically evoked C-fibre responses of WDR neurones in naïve rats [22] and behavioural studies reported no change in baseline threshold responses following spinal RvD1 treatment [61]. Our data build upon the recent report that intrathecal injection of RvD1 attenuates mechanical hypersensitivity in PCX-treated mice [21], and provides neurophysiological mechanisms underlying these antihyperalgesic effects seen in models of CINP.…”
Section: Discussionsupporting
confidence: 77%
“…Sexual dimorphism was reported for some of the resolvins in this previous study, specifically for RvD5, but not RvD1 or RvD2-mediated analgesia in the PCX model [ 21 ]. Previously, we reported that spinal administration of AT-RvD1 has robust inhibitory effects on noxious-evoked responses of spinal neurones in a model of acute inflammatory pain, but does not alter somatosensory processing in the spinal cord in naïve rats [ 22 ]. Here, we hypothesised that the sensitisation of spinal neuronal activity in the PCX model would be associated with changes in the spinal expression of genes encoding key neuroinflammatory markers and enzymes involved in the generation/catabolism of the resolvins, and that PCX-induced changes in spinal neuronal excitability would be responsive to spinal treatment with AT-RvD1.…”
Section: Introductionmentioning
confidence: 99%
“…AT-RvD1 reduces osteoarthritic pain (139), as does precursor 17-HDHA (140), prompting validation of their receptors (ALX/ FPR2 and ERV/CMKLR1) in rat models of osteoarthritis pain (141). Plasma RvD2 levels correlate with reduction in astrogliosis in spinal cord (141).…”
Section: Neural Systems and Arthritic Painmentioning
confidence: 97%
“…Aspirin‐triggered epimer AT‐RvD1 reduces osteoarthritic pain , as does its precursor, 17‐HDHA . Some SPM receptors (ALX/FPR2 and ERV/CMKLR1) are validated in murine osteoarthritic pain .…”
Section: Spm In Neural Systemsmentioning
confidence: 99%